The importance of caveolin as a target in the prevention and treatment of diabetic cardiomyopathy - Xia, Weiyi; Li, Xia; Wu, Qingping; Xu, Aimin; Zhang, Liangqing; Xia, Zhengyuan (Frontiers in Immunology, 2022)
The diabetic population has been increasing in the past decades and diabetic cardiomyopathy (DCM), a pathology that is defined by the presence of cardiac remodeling and dysfunction without conventional cardiac risk factors such as hypertension and coronary heart diseases, would eventually lead to fatal heart failure in the absence of effective treatment. Impaired insulin signaling, commonly known as insulin resistance, plays an important role in the development of DCM. A family of integral membrane proteins named caveolins (mainly caveolin-1 and caveolin-3 in the myocardium) and a protein hormone adiponectin (APN) have all been shown to be important for maintaining normal insulin signaling. Abnormalities in caveolins and APN have respectively been demonstrated to cause DCM. This review aims to summarize recent research findings of the roles and mechanisms of caveolins and APN in the development of DCM, and also explore the possible interplay between caveolins and APN.